In silico exploration of Isoxazole derivatives of usnic acid: novel therapeutic prospects against α-Amylase for diabetes treatment - Roney, Miah; Issahaku, Abdul Rashid; Huq, A. K. M. Moyeenul; Suhaila, Sapari; Fazira Ilyana, Abdul Razak; Wilhelm, Anke; Normaiza, Zamri; Sharmin, Sabrina; Islam, Md. Robiul; Mohd Fadhlizil Fasihi, Mohd Aluwi (Springer, 2024)
Diabetes mellitus (DM) a metabolic disorder characterized by high blood sugar levels causing damage to various organs over time. Current anti-diabetic drugs have limitations and side effects, prompting a search for new inhibitors targeting the α-amylase enzyme. This study aims to discover such inhibitors from thirty isoxazole derivatives of usnic acid using in silico approaches. The potential inhibitory effects of compounds were investigated using ADMET, molecular docking, molecular dynamic simulation, principal component analysis and density functional theory studies. ADMET analysis exhibited a wide range of physicochemical, pharmacokinetic, and drug-like qualities with no significant side effects which were then investigated using molecular docking experiment to determine the lead compound with the best binding affinity for the α-amylase enzyme. All compounds showed good binding affinity against α-amylase enzyme (−7.9 to −9.2 kcal/mol) where compound-13 showed the best binding affinity of −9.2 kcal/mol forming hydrogen bonds with Leu162, Tyr62, Glu233 and Asp300 amino acids. Furthermore, the binding posture and the stability of the compound-13-α-amylase enzyme complex was confirmed by molecular dynamic simulation experiment. Moreover, compound-13 showed binding energy value of −27.92 ± 5.61 kcal/mol, which indicated it could be an α-amylase inhibitor. Additionally, the reactivity of compound-13 was further confirmed by density functional theory analysis. The above findings suggest compound-13 to be a potential α-amylase inhibitor in DM. And setting the stage for further in vitro and in vivo experimental validation.